PENERAPAN PERMAINAN TRADISIONAL ENGKLEK DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK BINA GUNA - Eliya Desvarosa (Universitas Negeri Medan, 2016)
Abstract: Application Of Hopscotch Traditional Games Improve Cognitive Ability In Children Aged 5-6 Years In Kindergarten Bina Guna. The aim of research to determine the increase cognitive abilities of children through play hopscotch grouped B1 TK Bina Guna Terrain Academic Year 2015/2016. The subjects were children in group B1 amounted to 16 children. The results of the first cycle analysis of 16 children in the classical there are 4 children (25%) had cognitive abilities develop according to expectations, and 12 children (75%) have the cognitive abilities begin to develop value is 49.60. The second cycle of 16 children 4 children (25%) have the cognitive ability developed very well, 9 children (56%) had cognitive abilities develop according to expectations, and as many as three children (19%) had cognitive abilities began to grow with the average value of the class ie 68.36. Keywords: Traditional Games hopscotch, Cognitive Ability Abstrak : Penerapan Permainan Tradisional Engklek Dalam Meningkatkan Kemampuan Kognitif Anak Usia 5-6 Tahun Di TK Bina Guna. Tujuan penelitian untuk mengetahui peningkatan kemampuan kognitif anak melalui permainan engklek dikelompok B1 TK Bina Guna Medan Tahun Ajaran 2015/2016. Subjek penelitian adalah anak kelompok B1 berjumlah 16 anak. Hasil analisi siklus I dari 16 anak secara klasikal terdapat 4 anak (25%) memiliki kemampuan kognitif berkembang sesuai harapan, dan 12 anak (75%) memiliki kemampuan kognitif mulai berkembang dengan nilai yaitu 49,60. Siklus II dari 16 anak 4 anak (25%) memiliki kemampuan kognitif berkembang sangat baik, 9 anak (56%) memiliki kemampuan kognitif berkembang sesuai harapan, dan sebanyak 3 anak (19%) memiliki kemampuan kognitif mulai berkembang dengan nilai rata-rata kelas yaitu 68,36. Kata Kunci : Permainan Tradisional Engklek, Kemampuan Kognitif